“Los Costos de producción de muebles de la empresa home Solutions, de la ciudad de Riobamba, del primer semestre del 2016, para determinar sus precios de venta”. - Carchi Tingo, Grace Paola (2017)
The present research work is aimed at: Establish the costs of production of furnitures of the company HOME SOLUTIONS, of the Riobamba city, in the first half of 2016 to determine its sales prices, and sought contribute to providing solutions to problems that may exist within the entity. This research is structured in four chapters, the same that have developed as follows: In Chapter I, the Referential Framework is developed which includes the approach and formulation of the problem, the objectives to be achieved and the justification of the research. Chapter II corresponds to the Theoretical Framework, which is divided into units. In Unit I we find information from the Entity where the investigation was carried out. Unit II and III allow to know the theoretical bases of the Cost Accounting. Chapter III sets out the methods, techniques and instruments used in the investigation. Chapter IV including the results of the research, their analysis and interpretation. Chapter V describes the conclusions and issues the recommendations of the deviations found. Finally, the bibliography references are presented and the attachments of the investigation are attached.